Problems of Designing Complex Information Security System for Cloud Resources in the Republic of Belarus - V. P. Kochyn; A. V. Shantsou (Цифровая трансформация)
The influence of cloud computing on the information security of information resources during their transfer or deployment on cloud platforms is considered. The relevance of the problem of protecting information resources on cloud platforms, including for the Republic of Belarus, and the need to build an integrated system for protecting cloud resources are determined. The main features of cloud computing, affecting the security of information resources, are highlighted, such as: a model of joint responsibility of the provider and cloud clients to ensure information security; protection of the cloud platform infrastructure by the provider; the use of a reliable subsystem for identifying cloud clients; reliable isolation of virtual resources of cloud clients; the need for cloud clients to re-architect their applications and use encryption; Interaction between the cloud provider and clients when organizing audit procedures, incident response and implementing identification and authentication procedures in deployed services. General approaches to the implementation of an integrated information security system for cloud resources are proposed.